Competing influences on morphological modularity in biomechanical systems: a case study in mantis shrimp. Issue 3 (9th May 2016) - Anderson, Philip S. L.; Smith, Danielle C.; Patek, S. N.
SUMMARY: Related species that share similar biomechanical systems and segmentation patterns may exhibit different patterns of morphological covariation. We examined morphological covariation of the potent prey capture appendage of two mantis shrimp (Stomatopoda) species—a spearer ( Squilla empusa ) and smasher ( Gonodactylaceus falcatus ). We assessed three frameworks for modularity, two based on the biomechanics of the appendage and one based on its segmentation as a proxy for shared developmental pathways. We collected morphometric data from S. empusa, and compared morphological covariation patterns across the raptorial appendage with patterns from a new analysis of previously published morphometric data from G. falcatus . The relative importance of the different hypothetical influences differed between the two species, and was dependent on whether specimens were analyzed all together or subdivided based on sex or sub‐populations, including one particularly distinct population in the Gulf of Mexico. We also found an intriguing handedness pattern in which right‐hand appendages had a variable number of spines, whereas the left had a constant number of spines. Overall, our findings highlight the importance of testing multiple, alternative frameworks for morphological covariation and suggest that mantis shrimp experience contrasting influences on covariation depending on their feeding mechanisms.